Institutions and Venture Capital - Josh Lerner; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2012)
We survey the literature on venture capital and institutions and present a case study comparing the development of the venture capital market in the US to Sweden. Our literature survey underscores that the legal environment, financial market development, the tax system, labor market regulations, and public spending on research and development correlates with venture capital activities across countries. Our case study suggests these institutional differences led to the later development of an active venture capital market in Sweden compared to the US. In particular, a later development of financial markets and a heavier tax burden for entrepreneurs have played a key role.
Keywords: E02; G24; G28; N20; O16; O43; O57; 330; Financial market development; Institutions; IPOs; Labor markets; Legal environment; R&D; Taxation; Stock markets; Venture capital; Risikokapital; Institutionelle Infrastruktur; Vergleich; Schweden; USA